Change Management in Medical University Education in Romania in the Context of National and European Development Policies - Vladimir-Aurelian ENĂCHESCU; Ioana-Roxana TRAPIEL (Revista de Management Comparat International)
Innovation was also involved in the definition and types of medical systems, which have proven over time viability. The fundamental elements of any efficeient system, as a part of system management, like human resource, material resource, financial resource and not least, temporal resource, must be the principles on which it is founded. According to contemporary theories, priority is human resource and in this paper, we propose to analyze human resource training from this field, following analysis of change management in medical university education, coming up with a series of conclusions with the title of recommendations, for just such a future approach toward efficiency.